Oswaldella crassa Pena Cantero & Vervoort 1998 ... - Molinero, A. González; Peña Cantero, A. L. (Zenodo, 2015)
Oswaldella crassa Peña Cantero & Vervoort, 1998 Oswaldella crassa Peña Cantero & Vervoort, 1998: 33 –35, fig. 1; 2004: 822; Peña Cantero & García Carrascosa, 1998: 178; 1999: 214; Peña Cantero & Marques, 1999: 85. Ecology. Deep-water species, found at depths between 662 and 1120 m (Peña Cantero & Vervoort 1998). Distribution. Hitherto known only from the Bransfield Strait area (Peña Cantero & Vervoort 1998). ... : Published as part of Molinero, A. González & Peña Cantero, A. L., 2015, SEM study of species of Oswaldella Stechow, 1919 (Cnidaria, Hydrozoa, Kirchenpaueriidae), with an annotated checklist of the species of the genus, pp. 401-441 in Zootaxa 4052 (4) on page 434, DOI: 10.11646/zootaxa.4052.4.1, http://zenodo.org/record/245887 ...